Diseño de un sistema de costos para la empresa Emicalza, ubicada en la ciudad de Ambato, provincia de Tungurahua, periodo octubre – diciembre 2021 - Richards Ortega, Laura Domenica (2022)
The integrating project entitled "Design of a cost system for the Emicalza company, located in the city of Ambato, Tungurahua province, period October - December 2021", was developed with the purpose of establishing the total and unitary production cost, recognizing the cost elements that are used in each shoe production order, whether for a girl, a boy, a woman or a man. For the development of the project, 4 products were selected, considered as star articles; because they are the models with the greatest demand in the market and therefore register a greater number of production orders for their manufacture. The company has calculated its costs empirically, ignoring the items of investment, profitability and calculating the sale price in reference to the competition. The applied methodology has a quantitative approach, since numerical and mathematical processes were used through sequences which resulted in the determination of the total and unitary production cost; as well as the economic results for the period of October-December 2021; Bibliographic, field and descriptive research was used, using interview and observation as research techniques, managing to gather important information for the development of the study. The proposal for the design of the cost system for production orders was developed, where the total and unit costs were calculated, giving us as a result the costs made for each production order, determining the real cost and serving as a basis for the proper calculation. and opportune of the sale price, and at the same time allows management to make timely decisions that contribute to increasing the profit margin of the company, thereby tending to compete in the market against a diversity of factories that produce footwear of similar features. The cost system is also oriented to contribute to the efficient management of the company's resources and therefore to generate greater income for the industry.